The Power of Evidence of a Land Sale and Purchase Agreement (PPJB) in Full in Civil Dispute Cases - Shidqi, Sheehandea Talitha; Nursadi, Harsanto (LEGAL BRIEF, 2024)
In daily practice, the implementation of this sale and purchase does not necessarily produce a sale and purchase agreement, but is carried out by making an agreement which is usually referred to as a Sale and Purchase Binding Agreement or PPJB. The use of PPJB in relation to the transfer of land rights is generally due to obstacles or unfulfilled requirements in land sale and purchase transactions. PPJB has the legal force of perfect and binding evidence because PPJB was made before a notary is included in an authentic deed. This article uses a juridical-normative research method, namely by examining the application of rules or regulations related to the issues discussed in this article. This article discusses the existence of legal loopholes that can harm buyers in using PPJB, one of which is caused by the lack of further regulation in legislation. From this article it can be concluded that PPJB can be the basis for the legal transfer of land rights which therefore has perfect evidentiary legal force in civil disputes